PehN, a Polygalacturonase Homologue with a Low Hydrolase Activity, Is Coregulated with the Other Erwinia chrysanthemi Polygalacturonases - Hugouvieux-Cotte-Pattat, Nicole (American Society for Microbiology, 2002)
Erwinia chrysanthemi 3937 secretes an arsenal of pectinolytic enzymes, including at least eight endo-pectate lyases encoded by pel genes, which play a major role in the soft-rot disease caused by this bacterium on various plants. E. chrysanthemi also produces some hydrolases that cleave pectin. Three adjacent hydrolase genes, pehV, pehW, and pehX, encoding exo-poly-α-d-galacturonosidases, have been characterized. These enzymes liberate digalacturonides from the nonreducing end of pectin. We report the identification of a novel gene, named pehN, encoding a protein homologous to the glycosyl hydrolases of family 28, which includes mainly polygalacturonases. PehN has a low hydrolase activity on polygalacturonate and on various pectins. PehN action favors the activity of the secreted endo-pectate lyases, mainly PelB and PelC, and that of the periplasmic exo-pectate lyase PelX. However, removal of the pehN gene does not significantly alter the virulence of E. chrysanthemi. Regulation of pehN transcription was analyzed by using gene fusions. Like other pectinase genes, pehN transcription is dependent on several environmental conditions. It is induced by pectic catabolic products and is affected by growth phase, catabolite repression, osmolarity, anaerobiosis, nitrogen starvation, and the presence of calcium ions. The transcription of pehN is modulated by the repressor KdgR, which controls almost all the steps of pectin catabolism, and by cyclic AMP receptor protein (CRP), the global activator of sugar catabolism. The regulator PecS, which represses the transcription of the pel genes but activates that of pehV, pehW, and pehX, also activates transcription of pehN. The three regulators KdgR, PecS, and CRP act by direct interaction with the pehN promoter region. The sequences involved in the binding of these three regulators and of RNA polymerase have been precisely defined. Analysis of the simultaneous binding of these proteins indicates that CRP and RNA polymerase bind cooperatively and that the binding of KdgR could prevent pehN transcription. In contrast, the activator effect of PecS is not linked to competition with KdgR or to cooperation with CRP or RNA polymerase. This effect probably results from competition between PecS and an unidentified repressor involved in peh regulation.